2014
DOI: 10.1016/j.ymgmr.2014.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Non-depleting anti-CD4 monoclonal antibody induces immune tolerance to ERT in a murine model of Pompe disease

Abstract: Approximately 35–40% of patients with classic infantile Pompe disease treated with enzyme replacement therapy (ERT) develop high, sustained antibody titers against the therapeutic enzyme alglucosidase alfa, which abrogates the treatment efficacy. Induction of antigen-specific immune tolerance would greatly enhance ERT for these patients. Here we show that a short-course treatment with non-depleting anti-CD4 monoclonal antibody successfully induced long-term ERT-specific immune tolerance in Pompe disease mice. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…This is most likely the result of injecting mice with an ENPP1 protein that is recombinant and from a different species. Numerous rodent studies have shown that co-administration of anti-CD4 monoclonal antibody (mAb) can prevent ADA development in response to a protein replacement therapy and therefore this strategy was utilized here ( Rice and Bucy, 1995 ; Sun et al, 2014 ). Flow cytometry analysis confirmed >90% depletion of CD4 + T cells in peripheral blood from Asj-2J mice 7 days after a single 300 µg injection with an anti-CD4 mAb ( …”
Section: Resultsmentioning
confidence: 99%
“…This is most likely the result of injecting mice with an ENPP1 protein that is recombinant and from a different species. Numerous rodent studies have shown that co-administration of anti-CD4 monoclonal antibody (mAb) can prevent ADA development in response to a protein replacement therapy and therefore this strategy was utilized here ( Rice and Bucy, 1995 ; Sun et al, 2014 ). Flow cytometry analysis confirmed >90% depletion of CD4 + T cells in peripheral blood from Asj-2J mice 7 days after a single 300 µg injection with an anti-CD4 mAb ( …”
Section: Resultsmentioning
confidence: 99%
“…We also found that the induction of anti-GAA IgG1 responses assessed at 4 weeks after injection of rhGAA in Pompe animals was prevented by administration of a nonlytic anti-CD4 antibody given prior to ERT. 24 Given this effect of anti-CD4 to prevent immune responses, we elected The comparison was performed between the vector alone (G2) and vector plus three doses of anti-CD4 mAb (G4) groups. Group size as follows: G1 (n = 7), G2 (n = 11), G3 (n = 9), and G4 (n = 14).…”
Section: Resultsmentioning
confidence: 99%
“…[19][20][21][22][23] The use of nondepleting anti-CD4 mAb has also shown to decrease the immune response to introduced rhGAA in Pompe disease mice. 24 Anti-CD4 mAb in combination with cyclosporine was effective at suppressing anticapsid antibodies in response to administration of an AAV vector, although the effect was transient. 25 In the present study, we describe the inhibition of T helper cells by anti-CD4 mAb to achieve the control of immune responses to an AAV vector in GAA-KO mice.…”
Section: Introductionmentioning
confidence: 99%
“…Central tolerance has been induced in the C57Bl/6 N mouse by using an adenovirusassociated vector-expressing GAA (Chu et al 2010) to alter thymic GAA expression. Peripheral tolerance secondary to antigen specific Treg generation has been achieved with transplacental transfer of Fc-fused antigens (Gupta et al 2015), the useofIVIg(Loubakietal2015; Cousens et al 2014) and nondepleting anti-CD4 monoclonal antibodies (Sun et al 2014). More broad based therapies including the use of anti-CD3 antibodies (Ohashi et al 2012) and the SLE licensed, anti B cell activating factor (BAFF) ha veal so been studied with both ameliorating IRRS and ADA.…”
Section: Therapeutic Interventionsmentioning
confidence: 99%